FENOMENA HIJRAH SANTRI MILENIAL (Tinjauan Fenomenologis atas Tradisi Niqab di Kalangan Mahasiswi IDIA Al-Amien Prenduan) - Amalih, Ihwan; Maulidah, Tiffani (Universitas Al-Amien Prenduan, 2023)
at this time the meaning of hijrah became a trend that was much loved by millennial youth in the country. because hijrah that is presented has been packaged in social media content that is by millennial civilization. The hijrah that is happening at this time is also identical to the way they dress, one of which is the Niqa<b the result of research conducted by the Al vara Research Center in 2015 which states that more than 2% of Indonesian Muslim women wear the hijab to cover their faces or wear the Niqab. The main points of the articel presented in the formulation of this problem are first, How is the understanding of hijrah according to millennial IDIA Al-Amien Prenduan students? second, what motivates IDIA Al-Amien Prenduan students to Niqab?. This study aims to find out how IDIA Millennial Students Al-Amien Prenduan in expressing the meaning of Hijrah and their reasons for using Niqab. This Artikel is descriptive qualitative research using observation, interview, and documentation methods which are then analyzed to obtain data or information. The subjects of this study were taken from Niqab students at IDIA Al-Amien Prenduan. This articel concludes that hijrah is a movement or change not only in the body but also in the heart from bad things to good things to arrive at one goal, namely to get the pleasure of Allah SWT. While Niqab is a woman's face-covering clothing that only shows the two circles of her eyes. as a means to draw closer to Allah. one of them because he wants to keep his dignity as a woman.